Henoch-Scholein Purpura (HSP): A Clinico-etiological Study - Kareem, SN; Riyaz, N (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
<!–[if gte mso 9]> <![endif]–> Background: Henoch–Schönlein (HSP) is a small vessel vasculitis affecting skin and internal organs. Objectives: To determine the age group affected, etiological factors, clinical features, complications and association with other diseases. Methods: The study included 50 patients over a period of 3 years selected on the modified criteria by American College of Rheumatology. Clinical assessment was done and investigated for any focus of hidden infections especially Dental and ENT by respective departments. Associated conditions, complications and recurrence were also observed. Results: All patients had palpable purpura (pruritic in 58% and with hemorrhagic bullae in 6%) with upper respiratory tract prodrome (44%), joint involvement (94%) and gastrointestinal symptoms (90%). Precipitating factors were sore throat (74%), caries tooth (44%), drugs (30%) and food (16%) in varying combinations. On investigation 56% had raised ESR and 22% were with abnormal peripheral smears. All biopsies showed leucocytoclastic vasculitis. Occult blood in stool was detected in 10% and 2% showed Streptococci in throat swab culture. Renal involvement was 54% (RBC and albumin-42%, RBC alone-12%). One patient had intestinal perforation. Bleeding time, Clotting time, Platelet count, Cryoglobulin, ANA, Rheumatoid factor, HBs Ag, VDRL and X-ray chest were within normal limits. LE cell test was negative. Follow up study showed recurrence in 98%. Conclusion: HSP is a small vessel vasculitis in response to any unknown foreign or endogenous antigen. The age of onset varied from below 7 to 58 years, with most of them below 20. The most important clinical presentation was palpable purpura in lower extremities. GIT and joint involvement were more. Renal involvement found to be the most common complication. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10593 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014 pp.28-33 <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; –> <!–[endif] –>